International criminal law - Eishan Jan, Mohammad Naqib; Ahmad, Muhamad Hassan; Yaakob, Adnan (Thomsan Reuters Asia Sdn Bhd, 2023)
(30.001] International criminal law ("ICL") refers to a body of law that defines international crimes such as genocide, war crimes, crimes against humanity and the crime of aggression, among others; and the procedures to be applied in international criminal courts and tribunals. It generally places responsibility on individual persons and proscribes and punishes acts that are defined as crimes by international law. Sometimes, States can also be held responsible if the commission of the crime is attributable to it in one way or another. One of the main sources of ICL is the Rome Statute of the International Criminal Court ("ICC") which established the court in 1998 and became operational after the entry into force on July 1, 2002. (30.002] This chapter predominantly discusses the substantive international criminal law rather than the procedural aspect of it. Again, the discussion mainly focuses on core international crimes that fall within the jurisdiction of ICC, i.e. genocide, war crimes, crimes against humanity and the crime of aggression. In discussing these crimes, the chapter refers to the jurisprudence developed by international criminal courts, ad ho international criminal tribunals and hybrid international criminal tribunals.